2020
DOI: 10.7257/1053-816x.2020.40.6.277
|View full text |Cite
|
Sign up to set email alerts
|

It's About Time: The Temporal Burden of Lower Urinary Tract Symptoms Among Women

Abstract: Corresponding Author Beverly Rosa Williams, PhD, 205-789-5814 (day and evening), 205-934-7354 (fax),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…LUTS can occur for several years and followed by the emergence of anxiety and depression; in contrast, LUTS can occur for several years following the occurrence of anxiety and depression. Temporal relationship stands for a time-associated feature of LUTS, which describes a chronic progression of the disease 30 . A nationwide observational study by Huang et al 24 demonstrated the temporal bidirectional correlation.…”
Section: The Association and Temporal Bidirectional Relationship Betw...mentioning
confidence: 99%
See 1 more Smart Citation
“…LUTS can occur for several years and followed by the emergence of anxiety and depression; in contrast, LUTS can occur for several years following the occurrence of anxiety and depression. Temporal relationship stands for a time-associated feature of LUTS, which describes a chronic progression of the disease 30 . A nationwide observational study by Huang et al 24 demonstrated the temporal bidirectional correlation.…”
Section: The Association and Temporal Bidirectional Relationship Betw...mentioning
confidence: 99%
“…LUTS were proven as predictors for the development of mental disorders and subsequent poor QoL 31 . The burden of LUTS accumulates in daily lives in a temporal progressing process 30 . Higher anxiety-related disorders are more likely to be associated with functional loss among patients with LUTS 32,33 .…”
Section: The Association and Temporal Bidirectional Relationship Betw...mentioning
confidence: 99%